ANALYSIS OF ECONOMIC GROWTH FACTORS IN EAST JAVA CITIES SEEN FROM THE AVERAGE LENGTH OF SCHOOLING (RLS), HUMAN DEVELOPMENT INDEX (HDI) AND OPEN UNEMPLOYMENT RATE (TPT) BEFORE AND DURING THE PANDEMIC - Rohmadi; Doni Yusuf Bagaskara (Arsil Media, 2024)
This research aims to examine the effect of Average Years of Schooling (RLS), Human Development Index (HDI), and Open Unemployment Rate (TPT) on economic growth in East Java cities during the pre-pandemic years (2017-2019) and during the pandemic years (2020-2021). This study uses quantitative analysis techniques The tools used in this study are normality test, multicollinearity test, and multiple linear analysis. The results of this study indicate that before the pandemic the variables of Average Years of Schooling (RLS), Human Development Index (HDI) and Open Unemployment Rate (TPT) had a significant effect on econom Operating Expenses Operating Income Operating Expenses Operating Income Operating Expenses Operating Income ic growth in East Java cities while during the pandemic experienced a very significant change, namely Average Years of Schooling (RLS), Human Development Index (HDI) and Open Unemployment Rate (TPT) had no significant effect on economic growth in East Java cities.